TEACHERS’ ATTITUDE TOWARDS REMOTE LEARNING: ANALYSIS OF LATVIA’S CASE - Usca, Svetlana; Dzerviniks, Janis; Lubkina, Velta; Vindece, Aija; Poplavskis, Janis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The virtual environment has broken into all areas of our lives in the 21st century. Consequently, the issue of using IT at different levels of education, the usefulness or harmfulness of technologies, as well as the readiness of teachers to work with them is becoming more and more important. The Covid-19 pandemic activated the “technology revolution”, and Latvia's educational institutions switched to remote learning. Such a transformation revealed the strengths and weaknesses of education, as well as raised the issue of teachers' readiness for work in remote learning and attitude towards rapid change.The paper analyzes the data obtained by the State Research Programme “Life with COVID-19: Evaluation of overcoming the coronavirus crisis in Latvia and recommendations for social resilience in the future (CoLife)” on the attitude of Latvia's teachers towards the remote learning process.Research method: online survey of 559 general education teachers (K-12).